Pengaruh Pajak Daerah Dan Retribusi Daerah Terhadap Pendapatan Asli Daerah Kabupaten Sikka Tahun 2023 - Romoaldus Smayuni Nai (Universitas Kristen Indonesia Toraja, 2024)
An important implication of regional autonomy is fiscal decentralization where regions have the authority to regulate and manage their own affairs including regional financial management but the increasing needs of the regions cause the financing of government and development programs/activities to also be greater so that the Central Government is stricter in matters of Transfers to Regions and autonomous regions including Sikka Regency must be independent through Regional Original Revenue (PAD) but the slow development and public services in Sikka Regency in 2023 due to low PAD caused by low Regional Taxes which only contribute 67.34% and Regional Retributions which only contribute 50.77%. This Policy Paper aims to achieve the target of Local Tax and Local Retribution fulfillment in 2024 and develop policy recommendations to achieve the target. A quantitative approach is used to analyze the percentage of Local Tax and Local Retribution achievements in the PAD Structure of the Sikka Regency APBD in 2023. In-depth interviews with civil servants of the Regional Revenue Agency to identify challenges and perceptions related to the PAD management process were also conducted. The results of the analysis show the low realization of local taxes and levies in Sikka Regency with contributing factors including potential PAD not yet well recorded or fully collected, ineffective local tax and levy collection systems and poorly recorded taxpayer and levy databases. To overcome this, the policy recommendation is the Sikka Regent Regulation on the Technical Guidelines for the implementation of local tax and levy management as well as efforts to pick up the ball on tax and levy collection to the community.